Balancing workplace stress: empirical insights from the IMPRESS project - Lapiņa, Inga; Nikitina, Tatjana; Ozoliņa-Ozola, Iveta (Business, Management and Economics Engineering, 2026)
Purpose – This study aims to investigate the relationship between workplace stressors, resources, and perceived stress among employees by analysing survey data collected via the IMPRESS project. The objectives were to test the direct effects of stressors and resources on stress, and the moderating role of resources.Research methodology – Stressors, resources, and stress were measured using the Job Demands-Resources framework and the Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for statistical analysis.Findings – It was found that several stressors, particularly those related to roles and responsibilities, have a significant direct impact on stress levels.Research limitations – The study limitation is the geographical focus which being limited to Latvia.Practical implications – The principal conclusion is that managing stressors, e.g. role overload, role conflict and work-life balance, is critical, and well-defined work processes can significantly contribute to employee well-being. Originality/Value – The authors found that the COVID-19 pandemic did not significantly change workplace stressors, with roles and responsibilities remaining the dominant factor both before and during the pandemic.